Tungsten carbide and titanium carbide reinforced manganese steel

By using composite materials such as core-edge tungsten carbide titanium (W, Ti)C and tungsten carbide (WC) in the wear-resistant parts of manganese steel, combined with self-propagation high-temperature synthesis (SHS) reaction and heat treatment technology, manganese steel is solved The easy failure problem of wear-resistant components under extreme operating conditions achieves the best balance between wear resistance and impact resistance, extends service life and improves profitability.

CN119403636APending Publication Date: 2025-02-07SANDVIK SRP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380050989.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-06-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing manganese steel wear-resistant components are prone to premature failure under extreme operating conditions, and it is difficult to achieve the optimal balance between wear resistance and impact resistance.

Method used

Using composite materials containing core-edge tungsten carbide titanium (W, Ti)C, tungsten carbide (WC) and manganese steel matrix, the self-propagation high temperature synthesis (SHS) reaction and heat treatment technology are used to form an enhanced zone with excellent binding rate and Interface layer.

Benefits of technology

The optimal balance between wear resistance and impact resistance is achieved, the service life of wear-resistant components is extended, defects and cracks are reduced, and the structural integrity and profitability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403636A_ABST
    Figure CN119403636A_ABST
Patent Text Reader

Abstract

A composite material comprising: at least one reinforcement zone comprising tungsten carbide (WC) and titanium carbide (W, Ti) C and a manganese steel matrix; a manganese steel zone surrounding each of the reinforcement zones; and an interfacial layer between each of the reinforcement regions and the manganese steel region, characterized in that: the average grain size of (W, Ti) C particles in each of the reinforcement regions is between 0.2 and 2 [mu] m, and the average grain size of WC particles in each of the reinforcement regions is between 20 and 30 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite material based on reinforced manganese steel, a wear-resistant part made therefrom and a method for making the same. Background Art

[0002] A particular class of wear-resistant steels is often referred to as manganese steels or Hatfield steels. These materials are suitable for applications requiring high toughness and moderate wear resistance, including, for example, use as wear parts for crushers, which are subject to intense wear and dynamic surface pressures due to the rock crushing action. Wear occurs when rock material contacts the wear parts and strips material from the surface of the wear parts. In addition, the surface of the wear parts is subject to significantly high surface pressures that lead to fatigue and breakage of the wear parts.

[0003] Manganese steel or Hatfield steel is generally characterized by a certain amount of manganese, usually more than 11% by weight. However, a problem with manganese steel is that it is generally too soft for wear parts in modern crushers which are subjected to extreme operating conditions, which means that the service life of the wear parts is reduced and maintenance costs are increased. The problem to be solved is therefore to provide a manganese steel with enhanced wear resistance.

[0004] One known technical solution is to use particles with increased hardness to reinforce at least a portion of the manganese steel. WO 20200222662 discloses a composite material, however, the problem with this material is that it cannot provide an optimal balance between wear resistance and impact resistance, and more importantly, the bonding between the reinforcing particles and the manganese steel matrix is ​​weak, as well as the bonding between the reinforced area and the non-reinforced area, which leads to reduced wear resistance and premature failure of the wear-resistant parts.

[0005] The problem to be solved is therefore to provide a composite material useful for wear-resistant parts having an optimal balance between wear resistance and impact resistance, wherein the bonding between the reinforcing particles and the manganese matrix as well as the bonding between the reinforced and non-reinforced areas is improved in order to reduce defects and cracks that would lead to premature failure of the wear-resistant parts.

[0006] Additional composite materials are disclosed in US 2018 / 369905 and CN 111482579.

[0007] definition

[0008] A "catalyst" is a metal powder or mixture of metal powders that undergoes melting and forms a composite region matrix during the reaction of self-propagating high temperature synthesis (SHS). The basic role of the catalyst is to reduce the amount of energy dissipated during the SHS process.

[0009] A "compact" is a densified powder composition. Summary of the invention

[0010] The object of the present invention is to provide a new and improved composite material for wear-resistant parts. The object is achieved by providing a composite material comprising: at least one reinforcement zone, the reinforcement zone comprising core-edge tungsten titanium carbide (W,Ti)C, tungsten carbide (WC) and a manganese steel matrix; a manganese steel zone surrounding each of the reinforcement zones; and an interface layer between each of the reinforcement zones and the manganese steel zone; characterized in that the average grain size of the (W,Ti)C particles in each of the reinforcement zones is between 0.2-2µm, preferably between 1-2µm, and the WC particles in each of the reinforcement zones are between 20-30µm, preferably between 20-25µm.

[0011] Advantageously, this specifically selected grain size range provides an optimal balance between wear resistance and impact resistance. If the weight % and grain size of (W, Ti) C and WC in each of the reinforcement zones are too high, the composite material will be too brittle due to insufficient manganese steel between the hard metal grains in the matrix to provide the required toughness, and the material will therefore fail more easily. If the weight % and grain size of (W, Ti) C and WC in each of the reinforcement zones are too low, the composite material will have low hardness and will therefore not have sufficient wear resistance.

[0012] Preferably, the composite material contains between 80-98 wt% (W, Ti) C and between 0%-30% WC in each of the reinforcement zones. Preferably, between 90-98 wt% (W, Ti) C and 20%-30% WC, respectively; more preferably, between 94-98 wt% (W, Ti) C and 25%-30% WC, respectively. Advantageously, this provides an optimal balance between wear resistance and impact resistance. If the wt% of (W, Ti) C and WC in each of the reinforcement zones is too high, the composite material will be too brittle and more likely to fail. If the wt% of (W, Ti) C and WC in each of the reinforcement zones is too low, the composite material will have a low hardness and will therefore not have sufficient wear resistance.

[0013] Preferably, the composition of the manganese steel in the manganese steel zone has the following chemical composition by weight: carbon: 0.5 to 2.0%; manganese: 11% to 22%; silicon: 0.2% to 1.0%; chromium: 1% to 2%; nickel: up to 0.6%; molybdenum: up to 0.5%; and the balance Fe. Advantageously, the steel composition is characterized by the addition of appropriate amounts of microalloying elements, such as chromium, nickel and molybdenum, which cause high yield strength and high hardness, thereby resulting in increased wear resistance of the manganese steel.

[0014] Preferably, before work hardening, the Vickers hardness of the reinforced zone is between 900-1400 HV1 and the hardness of the manganese steel zone is between 300-400 HV1. Advantageously, the increased hardness in the reinforced zone makes the material more wear resistant.

[0015] Preferably, the thickness of each of the interface layers is greater than 150 μm, preferably greater than 100 μm, more preferably greater than 90 μm. Advantageously, the thickness of the interface layer or the thickness of the contact area between the manganese and the composite zone is indicative of the reaction propagation rate and the increase in heat generated due to the high combustion temperature occurring when in contact between the molten manganese steel and the insert. If the thickness is too large, the thermal conductivity in the composite zone increases, resulting in a faster heat dissipation to the inside of the composite zone, resulting in a high nucleation rate of (W, Ti) C and WC particles. If the thickness is too small, the thermal conductivity is small, which is favorable for growth, whereby the nucleation of (W, Ti) C and WC particles is less.

[0016] Preferably, the interface layer is free of defects. Advantageously, the absence of any defects in the interface layer means that there is a good bond between each of the manganese steel zone and the reinforcement zone, and thereby the structural integrity of the composite material is improved, which means that the life of the wear-resistant parts using the material is increased. In addition, the absence of any pores indicates that the composition has the ability to absorb excess heat and gas from the SHS process, and therefore indicates that the synthesis reaction has been successful.

[0017] Preferably, the bonding rate between the (W, Ti) C and WC grains in the reinforcement zone and the manganese steel is >99%, preferably >99.5%, and more preferably >99.9%. Advantageously, good bonding leads to excellent bonding between the composite zone and the manganese steel, thereby avoiding the formation of defects such as holes and cracks, and thus increasing wear resistance. If there is a 100% bonding rate, it means that there are no cracks or holes between the composite zone and the manganese steel.

[0018] Preferably, the volume of each of the enhancement zones is between 30 and 75 cm 3 The volume is determined using XRD. Advantageously, this size provides an optimal balance between wear resistance and impact resistance.

[0019] Preferably, at least 90%, more preferably at least 95% of the (W, Ti) C has a core-edge structure having a rounded shape with a composition gradient from the center to the outside of the particle, wherein the core is rich in Ti and the shell is rich in W. The WC grains in the reinforcement zone have irregular prismatic shapes including triangular to rectangular shapes. Advantageously, the rounded core-edge structure of the (W, Ti) C and the different prismatic shapes of the WC will help deflect cracks and prevent crack propagation, thereby improving the ductility and high wear resistance of the reinforcement zone. Advantageously, the prismatic shape of the WC will help deflect cracks and prevent crack propagation, thereby improving the ductility and high wear resistance of the reinforcement zone. At the same time, the core-edge shape will help reduce stress concentration under load.

[0020] Preferably, the distance between two adjacent reinforcement zones is between 0.5 and 50 μm, preferably between 0.5-10 μm, more preferably between 0.5-5 μm. Advantageously, this provides an optimal balance between wear resistance and impact resistance. If the reinforcement zones are too far apart, the wear resistance will not be high enough. If the reinforcement zones are too close together, the impact resistance will not be high enough.

[0021] Another aspect of the invention relates to a wear part comprising a composite material as described above or below. Advantageously, the presence of a reinforcement zone within the manganese zone will improve the wear resistance and thus the service life of the wear part, thereby increasing profitability.

[0022] Another aspect of the present invention relates to a method for manufacturing a composite material as described above or below, comprising the following steps: a) mixing 65-98 wt. % tungsten, 3-90 wt. % titanium, 3-20 wt. % carbon and 0-80 wt. % catalyst powder together; b) pressing the mixed powders together to form at least one compact; c) positioning and optionally fixing at least one compact inside a mold; d) pouring molten casting manganese steel into the mold to surround the at least one compact, thereby initiating a self-propagating high temperature synthesis (SHS) reaction to produce a casting; e) heat treating the casting; f) quenching the casting; wherein: in step b), the powder is pressed at a pressure between 400-700 MPa, preferably at a pressure between 500-600 MPa, and more preferably at a pressure between 550-600 MPa.

[0023] Advantageously, if this compacting pressure is used, the compact has a low density, which enables the manganese steel to penetrate more easily between the WC and (W,Ti)C grains and thereby leads to an improved bonding between the WC and TiC grains and the manganese steel. In addition, it avoids the generation of defects that would lead to premature failure of the wear-resistant component in which the composite material is used.

[0024] Preferably, the catalyst is selected from Fe, Mn, Ni, Mo, Cr, W, Al or mixtures thereof. Advantageously, the addition of a specific amount of catalyst will contribute to the strong stability of the austenite phase in the microstructure on the basis of good mechanical properties and high wear resistance. The catalyst addition will also act as a grain growth inhibitor leading to a fine microstructure. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : Line diagram showing the composition of the composite material.

[0026] Figure 2 : Shows SEM images taken of the enhanced region, with low magnification on the left and high magnification on the right.

[0027] Figure 3 : Shows SEM images taken of the interface layer, with low magnification on the left and high magnification on the right.

[0028] Figure 4 : shows the SEM image of the composite material.

[0029] Figure 5 : A perspective view showing a wear-resistant component.

[0030] Figure 6 : Shows the defects in sample E. DETAILED DESCRIPTION

[0031] Figure 1 A composite material 2 is shown, which includes at least one reinforcement zone 4, the reinforcement zone 4 including tungsten titanium carbide (W, Ti) C and tungsten carbide (WC) and a manganese steel matrix; a manganese steel zone 6, the manganese steel zone 6 surrounding each of the reinforcement zones 4; and an interface layer 8, the interface layer 8 is located between each of the reinforcement zones 4 and the manganese steel zone 6. In each of the reinforcement zones, (W, Ti) C and WC play a role in reinforcing the manganese steel matrix.

[0032] The average grain size of the (W, Ti) C particles in each of the reinforcement zones (4) is between 0.2-2 μm, preferably between 1-2 μm. The average grain size of the WC particles in each of the reinforcement zones (4) is between 20-30 μm, preferably between 20-25 μm.

[0033] The average grain size of (W,Ti)C and WC grains was determined by scanning electron microscopy (SEM) analysis, where several different areas of the sample were analyzed and the grain size was determined using Image J software. The average grain size was then calculated.

[0034] In one embodiment, the density of the reinforcement zone is 4.5-7.5 g / cm 3 Between, preferably between 6-7g / cm3 between.

[0035] In one embodiment, the density of the enhanced region is between 83% and 96% of the theoretical density, preferably between 85% and 94%.

[0036] Each interface layer 8 contains (W, Ti) C, WC and manganese steel, and can be distinguished from the reinforcement zone 4 due to the difference in shape and grain size of the (W, Ti) C and WC grains. The interface layer 8 can be distinguished from the reinforcement zone 4 by comparing the geometry and / or comparing the average grain size. If the geometry is compared, the reinforcement zone 4 contains >90% of WC grains with irregular prismatic geometry, while the interface layer 8 contains <5% of WC grains with rectangular prismatic geometry. If the WC grains have 4 sharp edges, they are considered to have a rectangular prismatic geometry. If the (W, Ti) C has a dark core (rich in Ti) and a light shell (rich in W), it is considered to have a core-edge structure with a rounded geometry. If the grain size is compared, the average WC grain size in the interface layer 8 is at least 5% smaller than the average WC grain size on the reinforcement zone 4.

[0037] Figure 2 Scanning electron microscope images using a MIRA3 TESCAN device are shown. A secondary electron detector (SE) with a high voltage of 15 KV and a working distance configuration of 9 mm was used. SEM images of (W,Ti)C and WC grains in the enhancement zone 4. Figure 3 SEM images of (W,Ti)C and WC grains in the interface layer 8 are shown. When comparing the two images, the different (W,Ti)C and WC grain geometries and sizes can be clearly seen.

[0038] In one embodiment, the weight % of (W, Ti) C in each of the reinforcement zones 4 is between 80-98%, more preferably between 90-98%, even more preferably between 94-98%, and the weight % of WC in each of the reinforcement zones 4 is between 0-30%, more preferably between 20%-30%, even more preferably between 25%-30%.

[0039] In one embodiment, the composition of the manganese steel in the manganese steel zone 6 has the following chemical composition by weight: carbon: 0.5 to 2.0%; manganese: 11% to 22%; silicon: 0.2% to 1.0%; chromium: 1% to 2%; nickel: up to 0.6%; molybdenum: up to 0.5%, and the balance Fe.

[0040] In one embodiment, the chemical composition of the manganese steel in each of the reinforcement zones 4 has the following chemical composition by weight: 1%-1.5% C, 11%-14% Mn, 0.4%-0.8% Si, 1.3%-2.0% Cr, 0.6% Ni, 0.065% P.

[0041] In one embodiment, the hardness of the reinforcement zone 4 is between 900-1400 HV1, preferably between 1000-1400 HV1. The hardness of the manganese steel zone 6 is between 300-400 HV1.

[0042] The hardness was measured using Vickers hardness mapping using 1 kgf and 15 seconds holding time on the polished samples. A microhardness tester, Matsuzawa, model MXT was used. The hardness measurement profile was performed starting from the non-reinforced area, moving to the interface layer, and then moving to the reinforced area.

[0043] In one embodiment, the width of the interface layer 6 is greater than 150 μm, preferably greater than 100 μm. Figure 4 SEM images of the reinforcement zone 4, the manganese steel zone 6 and the interface layer 8 taken at 15.0 kV and 219 magnification are shown. The width of the interface layer 6 is measured from a starting point 10, which is defined as a point adjacent to the manganese steel zone 6 and where (W, Ti) C and WC grains exist. The end point 12 is used to determine where the interface layer 8 ends and therefore where the reinforcement zone 8 begins, which is considered to be the position where the average grain size of the WC grains increases by 20% compared to the average WC grains measured at the starting point 10 and / or the position where the percentage of WC grains with a triangular prism shape increases by more than 90%.

[0044] In one embodiment, the interface layer 8 is free of defects when measured using an optical microscope at a magnification of 1000 times. Defects are considered to be cracks or holes.

[0045] In one embodiment, in the reinforcement zone 4, the bonding rate between the (W, Ti) C grains and the manganese steel and between WC and the manganese steel is >99%, preferably >99.5%, more preferably >99.9%, and most preferably 100%. The bonding rate % is determined by scanning electron microscopy, wherein the contact area and bonding rate between the (W, Ti) C grains or WC grains and the manganese steel are evaluated. In the reinforcement zone 4, the presence of cracks and / or defects between the (W, Ti) C grains and the manganese steel and between the WC and the manganese steel will reduce the bonding rate %.

[0046] In one embodiment, the volume of each of the enhancement zones 4 is between 30 and 75 cm 3For example, the length of the reinforcement zone 4 may be between 100-200 mm, preferably between 100-150 mm, the width may be between 20-30 mm, preferably between 20-25 mm, and the thickness may be between 15-30 mm, preferably between 15-25 mm, but is not limited thereto.

[0047] In one embodiment, >95%, preferably >98%, more preferably >99% of the (W, Ti) C grains in the reinforcement zone 4 have a circular shape. Preferably, the (W, Ti) C grains in the reinforcement zone are uniformly distributed in the manganese steel. In one embodiment, >95%, preferably >98%, more preferably >99% of the WC grains in the reinforcement zone 4 have a triangular prism shape. Preferably, the TiC grains in the reinforcement zone are uniformly distributed in the manganese steel.

[0048] In one embodiment, there are a plurality of reinforcing regions 4 and their interface regions 8, and the distance between two adjacent reinforcing regions 4 and their interface regions 8 is between 1-5 mm, preferably between 1-3 mm, and more preferably between 1-2 mm.

[0049] Figure 5 An example of a wear component 14 comprising a composite material 2 as described above or below is shown. For example, the wear component 2 may be, but is not limited to, a cone crusher, or a fixed jaw crusher, or a mobile jaw crusher or other material / rock processing unit configured to crush material. The reinforced area 4 is located at the location on the wear component 14 that is subject to the most high wear, such as on the crushing zone 18 of a cone crusher 16.

[0050] The method for manufacturing a composite material 2 as described above or below comprises the following steps: a) mixing together 65-98 wt.%, preferably 80-98 wt.% tungsten; 3-90 wt.%, preferably 10-90 wt.% titanium; 3-20 wt.%, preferably 3-20% carbon and 0-80%, preferably 10%-20% catalyst powder; b) pressing the mixed powders together to form at least one compact, using a pressing pressure between 400-700 MPa, preferably 500-600 MPa, and more preferably 550-600 MPa; c) positioning and optionally fixing at least one compact to the inside of a mold; d) pouring molten cast manganese steel into the mold to surround the at least one compact, thereby initiating a self-propagating high temperature synthesis (SHS) reaction to produce a casting; e) heat treating the casting; and then f) quenching the casting.

[0051] Preferably, the casting is treated at a temperature between 1400-1500°C and quenched with water. Preferably, the catalyst is selected from Fe, Co, Ni, Mo, Cr, W, Al or mixtures thereof. Carbon may be added in the form of graphite, amorphous graphite, carbonaceous material or mixtures thereof. For example, during casting, the compacts may be held in place using a metal fixing system to hold them in place during the casting process.

[0052] Example

[0053] Example 1 - Sample

[0054] Sample A is a comparative sample of non-reinforced manganese steel having the following composition: 1%-1.5% C, 11%-14% Mn, 0.4%-0.8% Si, 1.3%-2.0% Cr, 0.6% Ni, 0.065% P.

[0055] Sample AI is a sample of a composite material made by mixing tungsten, titanium, carbon and catalyst powders together. The mixed powder is pressed to form a compact, which is then placed in a mold, and molten manganese steel (having the following composition: 1%-1.5% C, 11%-14% Mn, 0.4%-0.8% Si, 1.3%-2.0% Cr, 0.6% Ni, 0.065%) is poured into the mold to surround the compact, thereby initiating a SHS reaction, and the casting is then heat treated at a temperature of 1450°C and then quenched with water. Table 1 shows a summary of the enhanced samples:

[0056]

[0057] It can be seen that if the permeability of the manganese steel is not good enough, the bonding rate is reduced and cracks and / or holes appear.

[0058] Example 2 - Hardness

[0059] Vickers hardness was measured by a microhardness tester (Matsuzawa, Model MXT) using 1 kgf and a holding time of 15 seconds. The hardness measurement profile was performed starting from the non-reinforced region, moving to the interface layer, and then moving to the reinforced region.

[0060] The hardness test results are shown in Table 2 below:

[0061]

[0062] It can be seen that the hardness is increased in the reinforced area of ​​the inventive sample compared to the comparative sample. Due to the large size of the pores, the hardness of E could not be determined.

[0063] Example 3 - Defects

[0064]

[0065] Defects were evaluated by using scanning electron microscopy analysis, where cracks and holes were identified. The inventive sample had small holes only in the reinforcement zone and no defects in the interface layer. Holes visible under an optical microscope at a magnification of 100 times were considered "large", and holes that began to be visible under an optical microscope at a magnification of 1000 times were considered "small".

Claims

1. A composite material (2), comprising: at least one reinforcement zone (4), the reinforcement zone (4) comprising a core-edge tungsten carbide titanium (W,Ti)C, tungsten carbide (WC) and manganese steel matrix, wherein the core is rich in titanium and the edge is rich in tungsten; a manganese steel zone (6) surrounding each of the reinforcement zones (4); and an interface layer (8), the interface layer (8) being located between each of the reinforcement zones (4) and the manganese steel zone (6); There are multiple reinforcement areas (4) and the distance between two adjacent reinforcement areas is between 1-5 mm; wherein the weight % of (W, Ti) C in each of the reinforcement zones (4) is between 80-98, and the weight % of WC in each of the reinforcement zones (4) is between 20-30; wherein before work hardening, the hardness of the reinforcement zone (4) is between 900-1400 HV1 and the hardness of the manganese steel zone (6) is between 300-400 HV1, wherein work hardening occurs when the manganese steel is subjected to a crushing force; Features: The average grain size of the (W, Ti) C particles in each of the reinforcement zones (4) is between 0.2 and 2 μm, and the average grain size of the WC particles in each of the reinforcement zones (4) is between 20 and 30 μm, wherein the average grain size of the (W, Ti) C and WC grains is determined by scanning electron microscopy (SEM) analysis, wherein the analysis is performed from several different areas of the sample, the grain size is determined using Image J software, and the average grain size is calculated from the determined grain size; and The density in the enhanced region (4) is between 83% and 96% of the theoretical density.

2. The composite material (2) according to claim 1, wherein the composition of the manganese steel in the manganese steel zone (6) has the following chemical composition by weight: Carbon: 0.5% to 2.0%; Manganese: 11% to 22%; Silicon: 0.2% to 1.0%; Chromium: 1% to 2%; Nickel: up to 0.6%; Molybdenum: up to 0.5%; and the balance Fe.

3. A composite material (2) according to any one of the preceding claims, wherein the thickness of each of the interface layers (8) is greater than 150 μm, wherein the thickness is determined by scanning electron microscopy (SEM) analysis, wherein the analysis is performed from several different areas of the sample, the particle size is determined using Image J software, and the average particle size is calculated from the determined particle size.

4. The composite material (2) according to any one of the preceding claims, wherein the interface layer (8) is free of defects when examined using an optical microscope at 1000 times magnification, wherein the defects are holes or cracks.

5. The composite material (2) according to any one of the preceding claims, wherein the bonding ratio between WC grains and manganese steel and the bonding ratio between (W,Ti)C grains and manganese steel in the reinforcement zone (4) is >99%.

6. A composite material (2) according to any one of the preceding claims, wherein the volume of each of the reinforcement zones is between 30 and 75 cm 3 wherein the volume is determined using X-ray diffraction.

7. The composite material (2) according to any one of the preceding claims, wherein at least 90% of the WC grains in the reinforcement zone (4) have an irregular prismatic shape.

8. A wear-resistant component (14) comprising the composite material (2) according to any one of claims 1 to 7.

9. A method for producing a composite material (2) according to any one of claims 1 to 7, comprising the following steps: a) mixing 65-98 wt % of tungsten, 3-90 wt % of titanium, 3-20 wt % of carbon and 0-80 wt % of catalyst powder, wherein the catalyst powder is selected from Fe, Ni, Mo, Cr, W, Al or a mixture thereof; b) pressing the mixed powders together to form at least one compact (20); c) positioning and fixing at least one green compact (20) into the interior of a mold (22); wherein the distance between two adjacent reinforcement regions is between 1 and 5 mm; d) pouring molten casting manganese steel (24) into the mold (22) to surround the at least one compact (20), thereby initiating a self-propagating high temperature synthesis (SHS) reaction to produce a casting (26); e) heat treating the casting (26); f) quenching the casting (26); Features: In step b), the powder is pressed at a pressure between 400-700 mPa.

Citation Information

Patent Citations

  • Powder Composition For The Manufacture Of Casting Inserts, Casting Insert And Method Of Obtaining Local Composite Zones In Castings

    US20180369905A1

  • Composite material based on alloys, manufactured in SITU, reinforced with tungsten carbide and methods of its production

    WO2020222662A1